The Influence of HOTS Problems in Developing Mathematical Literacy through Cooperative Learning Model (Jurusan Matematika FMIPA UNNES, 2023)
When students do math problems at school, it is found that students are still not able to do the given problems properly. This can happen due to the lack of mathematical literacy skills in students. However, mathematical literacy is one of the important skills to face the incoming challenge of this 21st and disruption century. This article aims to examine the influence of using HOTS problems on developing mathematical literacy skills through cooperative learning models. The method used in this article is through a literature study that collects several previous studies to answer the influence of using HOTS problems on developing mathematical literacy skills through cooperative learning models. The use of HOTS problems has an influence on developing mathematical literacy skills in cooperative learning models. So that teachers can provide and develop HOTS problems to improve students' mathematical literacy skills and students can also practice solving HOTS problems to improve mathematical literacy skills.